2020
DOI: 10.1111/acel.13148
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inbred mouse strains shows diverse phenotypic outcomes of intervertebral disc aging

Abstract: Intervertebral disc degeneration presents a wide spectrum of clinically degenerative disc phenotypes; however, the contribution of genetic background to the degenerative outcomes has not been established. We characterized the spinal phenotype of 3 mouse strains with varying cartilage‐regenerative potential at 6 and 23 months: C57BL/6, LG/J and SM/J. All strains showed different aging phenotypes. Importantly, LG/J mice showed an increased prevalence of dystrophic disc calcification in caudal discs with aging. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
111
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(121 citation statements)
references
References 32 publications
9
111
1
Order By: Relevance
“…ADAMTS-4 knockout mice, surprisingly, do not show any defects in skeletal development, growth, or remodelling, and no alterations in the growth of their long bones (Glasson et al, 2004). Likewise ADAMTS-5 knockout mice have no skeletal developmental abnormalities, although deletion of ADAMTS-5 effectively prevents cartilage destruction in a murine osteoarthritis model and is shown to protect from chronic tobacco smoke-induced disc degeneration (Ngo et al, 2017). These findings are consistent with the view that ADAMTS-5 is largely responsible for the turnover of murine aggrecan PRG4 knockout Increased torsional modulus and reduced transverse major diameter and height.…”
Section: Extracellular Matrix and Its Turnoversupporting
confidence: 72%
See 4 more Smart Citations
“…ADAMTS-4 knockout mice, surprisingly, do not show any defects in skeletal development, growth, or remodelling, and no alterations in the growth of their long bones (Glasson et al, 2004). Likewise ADAMTS-5 knockout mice have no skeletal developmental abnormalities, although deletion of ADAMTS-5 effectively prevents cartilage destruction in a murine osteoarthritis model and is shown to protect from chronic tobacco smoke-induced disc degeneration (Ngo et al, 2017). These findings are consistent with the view that ADAMTS-5 is largely responsible for the turnover of murine aggrecan PRG4 knockout Increased torsional modulus and reduced transverse major diameter and height.…”
Section: Extracellular Matrix and Its Turnoversupporting
confidence: 72%
“…Furthermore, domain IV of mouse perlecan contains less IgG repeats than human perlecan. Consequently, its core protein is ~ 40 kDa smaller than the human counterpart (Kallunki and Tryggvason, 1992;Noonan et al, 1991). Mouse perlecan also contains an RGD cell attachment sequence in domain III, which is absent in human perlecan (Chakravarti et al, 1995), although a cell adhesion site in domain IV has been identified in human perlecan (Farach-Carson et al, 2008) indicating that the overall functionality of the molecule is preserved between the species.…”
Section: Consideration Of Differences Between Murine and Human Proteomentioning
confidence: 99%
See 3 more Smart Citations